A busca do corpo ideal como sintoma contemporâneo: os significados do corpo para os adolescentes masculinos que freqüentam academias de ginástica na cidade de Montes Claros MG - Vera Lúcia Mendes Trabbold (2008)
The objective of this research goes into understanding the senses attributed to the body by the male adolescents, frequenting fitness centers in the city of Montes Claros MG, acting as motivating factors for the practice of physical training and for the consumption of energetic oranabolic steroids. Nine male adolescents were interviewed chosen from two fitness centers, aged between 14 and 20 years old. The method used was based on qualitative research, with interviews semi-structured as instrument and use of discursive practices and production of sense of Spink (2000) for the interpretation of the results, done from the analysis of the emergent categories. Theories of Psychology Human Development were used as theoretic referential. The body transformation in the puberty phase provoke changes in the corporal image, finding itself strange and in principle justifying the reasons why they attend regularly the gymnast academies: getting thin, growing fat, physical or psychological well-being or find happiness in physical exercises. However, the ultimate object was in fact to get a muscular body.What we find is a dissatisfaction with its corporal image live throughout its adolescence, not only in its initial moment, contradicting the literature (PAPALIA, 2000; PALACIOS &OLIVA, 2004, BEE, 1997). Said dissatisfaction results from the discrepancy between the real body image and the ideal body image (LEVISKY, 1998), based in a pos-modern esthetic corporal, deeply narcissist, (OUTEIRAL, 2000; MALYSSE, 2006) propagated and by mediareinforced. The self-esteem and well-fare of those adolescents will depend on the group of their pairs and pairs affective recognizing them as owners of such ideal body image (HARGREAVES E TIGGEMANN, 2006). The academy is the place where you can get health, change the physical form, gain body, take care of the body and gain muscles. Adolescents associate musculature with health to disguise vanity, the way it is more accepted by our society. Within those young 7 of them started the frequency in the fitness centers between the 14th and 15th years of age, and not before, afraid that the physical exercise might result in low stature (RIBEIRO, 2006). The construction of the sexual and the gender identityis strongly affected by the forms of perception of the gender norms. Other forms quoted to obtain the ideal body image were the sports, according to two of them, and five adolescents quoted the use of anabolic steroids by their cousins, colleagues and friends, confirming the researches on the increase of use among male adolescents (RIBEIRO, 2002; SOUZA &FISBERG, 2002, ASSUNÇÃO, 2002; ARAUJO e Cols, 2002; IRIART & ANDRADE, 2002). One of them uses the formula to loose weight with energetic, counter indicated in the adolescence. The anabolic quoted were Deca-Durabolin ® OR Durateston ® (RIBEIRO, 2006) and two other which cannot be found in the literature. They are used for the quick wayof muscular gain, circulating those information among the adolescents frequenting the fitness centers (SABINO, 2005; IRIART & ANDRADE, 2002). Sold without medical prescription and the more expensive are divided among the adolescents. Factors protecting the adolescentsfrom the abuse of the steroids were quoted as good familiar relationship, frequency of the fitness centers of good and with good self-esteem.